2010
DOI: 10.1128/jcm.00410-10
|View full text |Cite
|
Sign up to set email alerts
|

Serotype-Specific Typing Antisera for Pneumococcal Serogroup 6 Serotypes 6A, 6B, and 6C

Abstract: ᰔStreptococcus pneumoniae strains can express one of at least 92 capsular serotypes. To our knowledge, our laboratory is one of two that maintain antisera for resolution of the first 90 discovered pneumococcal serotypes (4; unpublished data). Recently, the evaluation of serogroup 6 isolates using monoclonal antibodies led to the discovery of the 91st serotype, 6C (7), which has become the prevalent invasive serogroup 6 serotype within the United States (2, 9). The pneumococcal 7-valent conjugate vaccine (PCV7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Hare et al, who recently reported similar atypical reactions with some serotype 6A isolates, referred to them as "dodgy 6As" and also showed that they were serotype 6C (3). Melnick et al produced 6d antiserum specific for 6C and an absorbed 6b antiserum specific for 6A, which give the same results as ours for serotype 6C (9).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Hare et al, who recently reported similar atypical reactions with some serotype 6A isolates, referred to them as "dodgy 6As" and also showed that they were serotype 6C (3). Melnick et al produced 6d antiserum specific for 6C and an absorbed 6b antiserum specific for 6A, which give the same results as ours for serotype 6C (9).…”
supporting
confidence: 70%
“…The use of this factor antiserum for identification of serotype 6C has recently been validated (4,9). We also compared "old" (purchased before 2009) and "new" factor 6b and pool B antisera (purchased in 2009).…”
mentioning
confidence: 99%
“…11,24 All isolates (2007-2013) and culture-negative cases (2011-2013) of serogroup 6 were screened for 6A, 6B, 6C and 6D by specific antisera and PCR, respectively. [25][26][27] However, serotypes within serogroup 18 and 6, detected by PCR of culture-negative CSF specimens collected during 2007-2010, could not be differentiated. These serogroups were classified to types by extrapolation based on the proportional distribution of serotypes of 18 (A, B, C and F) and 6 (A, B, C and D) among culture-positive isolates from meningitis cases.…”
Section: Laboratory Methodsmentioning
confidence: 76%
“…We have recently shown that we are capable of resolving all four known serogroup 6 serotypes, including 6D (Mercado et al, 2011), using our specific factor sera prepared against serotypes 6A, 6B and 6C (Melnick et al, 2010).…”
Section: Resultsmentioning
confidence: 99%